2015
DOI: 10.1890/14-1776.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical stress modifies top‐down and bottom‐up forcing on plant growth and reproduction in a coastal ecosystem

Abstract: Bottom-up and top-down effects act together to exert strong control over plant growth and reproduction, but how physical stress modifies those interactive forces remains unclear. Even though empirical evidence is scarce, theory predicts that the importance of both top-down- and bottom-up forces may decrease as physical stress increases. Here, we experimentally evaluate in the field the separate and interactive effect of salinity, nutrient availability, and crab herbivory on plant above- and belowground biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…, Daleo et al. ). Fertilizer was spread into six artificial holes (5 cm deep, 1 cm diameter) evenly distributed in each plot that were then filled with mud.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…, Daleo et al. ). Fertilizer was spread into six artificial holes (5 cm deep, 1 cm diameter) evenly distributed in each plot that were then filled with mud.…”
Section: Methodsmentioning
confidence: 98%
“…Crab-exclusion plots were surrounded using a plastic mesh (10 mm opening) fence 0.6 m high and supported by iron stakes. Crab exclosures have been widely used in this system and the use of cage controls revealed that there are no associated cage artifacts (Daleo et al 2015). Salt addition plots received 20 g (~40 g/m 2 ) of commercial pelletized salt spread superficially every 2 weeks.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…It is later recognized that both top‐down (e.g., predators) and bottom‐up (e.g., nutrient availability) driving forces can act in concert with communities after decades of intense debate (Daleo et al. , Vidal and Murphy ). Disentangling the relative contributions of top‐down and bottom‐up forces can help explain the abundance and patterns of plants.…”
Section: Introductionmentioning
confidence: 99%